2006
DOI: 10.1086/508534
|View full text |Cite
|
Sign up to set email alerts
|

The Spiderweb Galaxy: A Forming Massive Cluster Galaxy at z ~ 2

Abstract: We present a deep image of the radio galaxy MRC 1138Ϫ262 taken with the Hubble Space Telescope (HST) at a redshift of . The galaxy is known to have properties of a cD galaxy progenitor and be surrounded z p 2.2 by a 3 Mpc-sized structure, identified with a protocluster. The morphology shown on the new deep HST ACS image is reminiscent of a spider's web. More than 10 individual clumpy features are observed, apparently starforming satellite galaxies in the process of merging with the progenitor of a dominant clu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
196
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(205 citation statements)
references
References 26 publications
(42 reference statements)
8
196
1
Order By: Relevance
“…Spectroscopy is required to prove the association of these objects with the radio galaxy but their physical closeness and colours strongly suggest that they are associated with MRC 0156-252. The scale of this system is similar to the structure associated with PKS 1138-262 i.e., about 15 (see Miley et al 2006, Fig. 2).…”
Section: The Yhk-selected Galaxiessupporting
confidence: 57%
“…Spectroscopy is required to prove the association of these objects with the radio galaxy but their physical closeness and colours strongly suggest that they are associated with MRC 0156-252. The scale of this system is similar to the structure associated with PKS 1138-262 i.e., about 15 (see Miley et al 2006, Fig. 2).…”
Section: The Yhk-selected Galaxiessupporting
confidence: 57%
“…Extended gas disks within the radio galaxy Best (2000) pointed out that radio galaxies with very extended radio sources are particularly good candidates for being cluster central galaxies because the pressure from the Mpc-scale intracluster medium boosts the luminosity of the radio source even for comparably extended jets (see also Athreya et al 1998;Klamer et al 2006). Many authors have previously suggested that the progenitors of brightest cluster galaxies are likely to be found among HzRGs (e.g., Pentericci et al 2001;Miley et al 2006;Hatch et al 2009), andWylezalek et al (2013) find from IRAC imaging that TXS 2353-003 is even associated with the most strongly pronounced overdensity within their sample.…”
Section: Partial Agn Illumination Of Ambient Halo Cloudsmentioning
confidence: 99%
“…The z and H-band data were reduced in a standard manner. We further supplemented the data set with superb resolution imaging by the ACS on-board the HST (Miley et al 2006). We retrieved the pipeline reduced g and I band images from the Hubble Legacy Archive.…”
Section: Pks1138mentioning
confidence: 99%